The Screen of the Migrant Body: Technologies of Abjection and the “So-Called” Rape of Amarinthos - Papailias, Penelope (The Greek Review of Social Research, 2013)
This article examines a seminal moment in the violent mediatized exposure of the female migrant body in contemporary Greek society: the 2006 video rape of a student of Bulgarian origin in Amarinthos, Evia. This cyberbullying incident demonstrated how the contemporary exercise of gender and ethnic violence relies on technological practices of optical targeting, surveillance, spectacularization and voyeurism by sovereign citizens. After initial intense media coverage, however, the “truth” of the rape gradually came into question. As a process of abjection, the rape transformed an immigrant neighbor, classmate, even girlfriend—a familiar stranger—into an abhorrent Other, whose inseparability from the self, in fact, is confirmed by this ongoing repudiation.